2020
DOI: 10.1364/oe.414050
|View full text |Cite
|
Sign up to set email alerts
|

Improving characteristic band selection in leaf biochemical property estimation considering interrelations among biochemical parameters based on the PROSPECT-D model

Abstract: At present, many studies have mainly focused on analyzing the sensitivity and correlation to select characteristic bands. However, the interrelations between biochemical parameters were ignored, which may significantly influence the accuracy of biochemical concentration retrieval. The study aims to propose a new band selection method and to focus on the improving magnitude of characteristic band combination in leaf trait estimation when taking interrelations among different traits into consideration. Thus, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…2021, 13, 1394. https://doi.org/10.3390/rs13071394 https://www.mdpi.com/journal/remotesensing Remote Sens. 2021, 13, 1394 2 of 27 distribution of crops, and their temporal variation throughout the growing season, plays an essential role in the sustainable management and development of agricultural practice, crop biophysical and biochemical variable estimation, crop yield prediction, evaluation of ecosystem services and food security [3][4][5][6]. The ground survey method to obtain this vital information is usually time-consuming, labour intensive and expensive [7].…”
Section: Introductionmentioning
confidence: 99%
“…2021, 13, 1394. https://doi.org/10.3390/rs13071394 https://www.mdpi.com/journal/remotesensing Remote Sens. 2021, 13, 1394 2 of 27 distribution of crops, and their temporal variation throughout the growing season, plays an essential role in the sustainable management and development of agricultural practice, crop biophysical and biochemical variable estimation, crop yield prediction, evaluation of ecosystem services and food security [3][4][5][6]. The ground survey method to obtain this vital information is usually time-consuming, labour intensive and expensive [7].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, 2019;N. Liu et al, 2020;Yang et al, 2021) and satellite-or air-borne remote-sensing data are more of professional applications concerning large scale assessment and then their potentials should be assessed in the future works.…”
Section: Discussionmentioning
confidence: 99%
“…By investigating haze pollution events with low visibility in the northern Indian city of Chandigarh, Ravindra et al [40] found a high correlation between high PM 2.5 concentrations and CO and No x during haze pollution, indicating that the sources are mainly biomass burning, fossil fuel combustion, and vehicle exhaust emissions. The concentration of O 3 shows a significant daily variation, with high midday concentrations and low nighttime concentrations, indicating significant photochemical processes [41][42][43]. To investigate the effect of meteorological conditions on the variation of air quality, the temperature, RH, WS, WD and pressure during the haze pollution event are analyzed in Figure 4.…”
Section: Overview Of Winter Haze Pollution In Jinanmentioning
confidence: 99%